2022
DOI: 10.1111/1756-185x.14291
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and correlates of depression in Korean adults with rheumatoid arthritis: Results from the Korea National Health and Nutrition Examination Surveys

Abstract: Purpose This study aimed to investigate the prevalence and correlates of depression in Korean patients with rheumatoid arthritis (RA). Methods We analyzed the data of the Korean National Health and Nutrition Examination Survey (KNHANES). The sociodemographic, clinical, and psychiatric variables were compared between the RA group (n = 277) and the gender‐ and age‐matched non‐RA group (n = 1068). Participants in the RA group who had a Patient Health Questionnaire‐9 (PHQ‐9) score of 10 or more were sub‐categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our results associating limitations in activities of daily living with depressive symptoms in older patients with arthritis is consistent with the findings of many previous studies. A study in Korea found that patients with RA were three times more likely to experience depression, as assessed by the PHQ-9, if they also had limitations in activities of daily living (34). A study in Taiwan Province of China also associated higher functional ability with lower levels of depression measured by the Geriatric Depression Scale (38).…”
Section: Factors Associated With Depressive Symptoms In Patients With...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results associating limitations in activities of daily living with depressive symptoms in older patients with arthritis is consistent with the findings of many previous studies. A study in Korea found that patients with RA were three times more likely to experience depression, as assessed by the PHQ-9, if they also had limitations in activities of daily living (34). A study in Taiwan Province of China also associated higher functional ability with lower levels of depression measured by the Geriatric Depression Scale (38).…”
Section: Factors Associated With Depressive Symptoms In Patients With...mentioning
confidence: 99%
“…The United States National Health Interview Survey (2015-2017) found that the prevalence of depressive symptoms classified based on a frequency question and an intensity question of depressed feeling in patients with arthritis and more than two chronic conditions was double that of patients with one or two conditions (28). The Korea National Health and Nutrition Examination Survey revealed that patients with RA with three or more comorbidities had five-fold higher odds of depression as measured by the PHQ-9 than those without (34). In addition to its relationship with depressive symptoms, multimorbidity has been found to be related to limitations in activities of daily living in China, India, and the United States (35)(36)(37).…”
Section: Factors Associated With Depressive Symptoms In Patients With...mentioning
confidence: 99%
“…Patients with RA are more likely to experience depression and poor quality of life (QoL). The prevalence of depression in patients with RA is estimated to be 14.8%–38.8%, which is significantly higher than that in the general population 1,2 . In a meta‐analysis, patients with RA who were depressed had poorer health‐related QoL, 3 higher RA disease activity, 4 and were less likely to respond to treatment or achieve disease remission 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the mortality rate of patients with RA is still higher than in the general population 7 . Several comorbidities have also been reported in patients with RA, including depression, 8 asthma, cardiovascular events, and malignancies 9 . Advances in diagnostic tools and the availability of new therapeutic options have been of utmost importance for improving patient outcomes 10 .…”
Section: Introductionmentioning
confidence: 99%